Operation Bounce House - Dinniman, Matt (Ace, 2026)
"A man must fight for his planet against impossible odds when gamers from Earth attempt to remotely annihilate it in this epic, fast-paced novel from the New York Times bestselling author of the smash-hit Dungeon Crawler Carl. All colonist Oliver Lewis ever wanted to do is run the family ranch with his sister, maybe play a gig or two with his band, and keep his family's aging fleet of intelligent agriculture bots ticking as long as possible. As a fan of Earth television and culture, he figures it will be a good thing when the transfer gate finally opens all the way and restores instant travel and full communication between Earth and his planet, New Sonora. But there's a complication. Even though the settlers were promised they'd be left in peace, Earth's government now has other plans. The colossal Apex Corporation is hired to commence an "eviction action." But maximizing profits will always be Apex's number one priority. Why spend money printing and deploying their own AI soldiers when they can turn it into a game? Why not charge bored Earthers for the opportunity to design their own war machines and remotely pilot them from the comfort of their own homes? The game is called Operation Bounce House. Oliver and his friends soon find themselves fighting for their lives against machines piloted by gamers who've paid a premium for the privilege. With the help of an old book from his grandfather and a bucket of rusty parts, Oliver is determined to defend the only home he's ever known"-- Provided by publisher.